2016
DOI: 10.1186/s13013-016-0103-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of scoliotic deformity on spine kinematics in adolescents

Abstract: BackgroundWhile adolescent idiopathic scoliosis (AIS) produces well characterized deformation in spinal form, the effect on spinal function, namely mobility, is not well known. Better understanding of scoliotic spinal mobility could yield better treatment targets and diagnoses. The purpose of this study was to characterize the spinal mobility differences due to AIS. It was hypothesized that the AIS group would exhibit reduced mobility compared to the typical adolescent (TA) group.MethodsEleven adolescents with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…However, the major limitation of the study is that we cannot account for the possibility that spinal curves themselves could reduce the overall length of spine or mechanical impair spinal flexibility, which both may affect the ability to palm the floor. While previous studies have shown the spine is more flexible in mild scoliosis [24], spines with larger curve angle and apical vertebral rotation show less flexibility, at least on supine brending films[25]. It remains unknown whether the reduced flexibility of severe curves is itself present prior to curve progression are is a secondary consequence of mechanical changes due to the scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the major limitation of the study is that we cannot account for the possibility that spinal curves themselves could reduce the overall length of spine or mechanical impair spinal flexibility, which both may affect the ability to palm the floor. While previous studies have shown the spine is more flexible in mild scoliosis [24], spines with larger curve angle and apical vertebral rotation show less flexibility, at least on supine brending films[25]. It remains unknown whether the reduced flexibility of severe curves is itself present prior to curve progression are is a secondary consequence of mechanical changes due to the scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…The results of both approaches reflected deviations from the straight posture with increased curvature values, but the radius of curvature approach (k o ) was more heavily influenced by segment length. Additionally, the vector approach (k b ) is more like outcome measures already used in clinical applications, such as joint rotations and spine curvature [21][22][23]. Therefore, the vector approach was deemed more appropriate in translation to clinical devices.…”
Section: Kinematic Discussionmentioning
confidence: 99%
“…For instance, LBP accounts for ~40% of lost workdays with an estimated direct healthcare expenditure of $50–90 billion annually in the US (Guo et al, 1999 ; Yang et al, 2016 ). Many spinal disorders, including idiopathic back pain, degenerative disc disease, lumbar spinal stenosis, vertebral fractures (traumatic or osteoporotic), spine deformity, and muscle imbalance (e.g., myopathy, muscle dystrophy), can alter the kinematics and posture of the trunk (Al-Eisa et al, 2006 ; Briggs et al, 2007 ; Mahaudens et al, 2009 ; Galvis et al, 2016 ; Kuwahara et al, 2016 ; Schmid et al, 2016 ; Basques et al, 2017 ; Christe et al, 2017 ; Chun et al, 2017 ; Crawford et al, 2018 ; Igawa et al, 2018 ). Therefore, objective measurements of trunk kinematics and posture are useful in evaluating the functional impacts of spinal disorders and the development of novel clinical treatments.…”
Section: Introductionmentioning
confidence: 99%